2016
DOI: 10.3390/ma9120991
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Porous Materials from Natural/Synthetic Biopolymers and Their Composites

Abstract: Biopolymers and their applications have been widely studied in recent years. Replacing the oil based polymer materials with biopolymers in a sustainable manner might give not only a competitive advantage but, in addition, they possess unique properties which cannot be emulated by conventional polymers. This review covers the fabrication of porous materials from natural biopolymers (cellulose, chitosan, collagen), synthetic biopolymers (poly(lactic acid), poly(lactic-co-glycolic acid)) and their composite mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(86 citation statements)
references
References 104 publications
1
82
0
3
Order By: Relevance
“…One of such techniques is the micro-molding method adopted by Soumaya et al 2015 in fabricating porous polymethyl hydrosiloxane structure using porous silicon scaffolds. Several other researchers including but not limited to Aizawa 2018, Udeni et al 2016, Xiao-Yu 2017, He et al 2012, Jang et al 2014and Jun et al 2017 in their research reports, also confirmed the possibility of designing and developing useful porous materials of desired properties. In everyday life, the emerging properties of enormous practical importance exhibited by fabricated porous materials have led to a pronounced increase in the range of their applications from applied sciences to medical diagnosis and engineering.…”
Section: Introductionmentioning
confidence: 71%
“…One of such techniques is the micro-molding method adopted by Soumaya et al 2015 in fabricating porous polymethyl hydrosiloxane structure using porous silicon scaffolds. Several other researchers including but not limited to Aizawa 2018, Udeni et al 2016, Xiao-Yu 2017, He et al 2012, Jang et al 2014and Jun et al 2017 in their research reports, also confirmed the possibility of designing and developing useful porous materials of desired properties. In everyday life, the emerging properties of enormous practical importance exhibited by fabricated porous materials have led to a pronounced increase in the range of their applications from applied sciences to medical diagnosis and engineering.…”
Section: Introductionmentioning
confidence: 71%
“…Collagen is a structural protein and exists in the most part of connective tissues, skin, bone, cartilage, and tendons. This protein as main protein type of the extracellular matrix provides structural, mechanical and biochemical properties (Daei‐farshbaf et al, ; Sampath, Ching, Chuah, Sabariah, & Lin, ). Baheiraei et al were fabricated and investigated collagen (COL) and collagen/beta tricalcium phosphate (COL/β‐TCP) scaffolds potential for use in bone tissue engineering and their results demonstrated that osteogenic markers were greatly increased in mouse BM‐MSCs cultured on composited scaffolds and also assisting to rapid vascularization (Baheiraei et al, ).…”
Section: Nanofibrous Fabrication Methodsmentioning
confidence: 99%
“…Chitosan exists in the exoskeleton crabs and shrimps and the bone of cuttlefish and squids, it is second numerous biopolymer in nature and also, it is a major abundant of fungi cell wall (Ardeshirylajmi, Delgoshaie, Mirzaei, & Khojasteh, ; Sampath et al, ). Developing the chitosan scaffold performance by employing suitable composites and materials showed promising potential of this kind of scaffold for bone tissue engineering applications.…”
Section: Nanofibrous Fabrication Methodsmentioning
confidence: 99%
See 2 more Smart Citations